Mutations in the FOG2/ZFPM2 gene are associated with anomalies of human testis determination. (18th February 2014) - Bashamboo, Anu; Brauner, Raja; Bignon-Topalovic, Joelle; Lortat-Jacob, Stephen; Karageorgou, Vasiliki; Lourenco, Diana; Guffanti, Alessandro; McElreavey, Ken
Abstract : In recent years, considerable advances have been made in our understanding of genetics of mammalian gonad development; however, the underlying genetic aetiology in the majority of patients with 46, XY disorders of sex development (DSD) still remains unknown. Based on mouse models, it has been hypothesized that haploinsufficiency of the Friend of GATA 2 ( FOG2 ) gene could lead to 46, XY gonadal dysgenesis on specific inbred genetic backgrounds. Using whole exome sequencing, we identified independent missense mutations in FOG2 in two patients with 46, XY gonadal dysgenesis. One patient carried a non-synonymous heterozygous mutation (p.S402R), while the other patient carried a heterozygous p.R260Q mutation and a homozygous p.M544I mutation. Functional studies indicated that the failure of testis development in these cases could be explained by the impaired ability of the mutant FOG2 proteins to interact with a known regulator of early testis development, GATA4. This is the first example of mutations in the coding sequence of FOG2 associated with 46, XY DSD in human and adds to the list of genes in the human known to be associated with DSD.